GLI1 regulates a novel neuropilin‐2/α6β1 integrin based autocrine pathway that contributes to breast cancer initiation - Hira Lal Goel; Bryan Pursell; Cheng Chang; Leslie M. Shaw; Junhao Mao; Karl Simin; Prashant Kumar; Craig W. Vander Kooi; Leonard D. Shultz; Dale L. Greiner; Jens Henrik Norum; Rune Toftgard; et al. (EMBO Molecular Medicine)
Abstract The characterization of cells with tumour initiating potential is significant for advancing our understanding of cancer and improving therapy. Aggressive, triple‐negative breast cancers (TNBCs) are enriched for tumour‐initiating cells (TICs). We investigated that hypothesis that VEGF receptors expressed on TNBC cells mediate autocrine signalling that contributes to tumour initiation. We discovered the VEGF receptor neuropilin‐2 (NRP2) is expressed preferentially on TICs, involved in the genesis of TNBCs and necessary for tumour initiation. The mechanism by which NRP2 signalling promotes tumour initiation involves stimulation of the α6β1 integrin, focal adhesion kinase‐mediated activation of Ras/MEK signalling and consequent expression of the Hedgehog effector GLI1. GLI1 also induces BMI‐1, a key stem cell factor, and it enhances NRP2 expression and the function of α6β1, establishing an autocrine loop. NRP2 can be targeted in vivo to retard tumour initiation. These findings reveal a novel autocrine pathway involving VEGF/NRP2, α6β1 and GLI1 that contributes to the initiation of TNBC. They also support the feasibility of NRP2‐based therapy for the treatment of TNBC that targets and impedes the function of TICs. → See accompanying article http://dx.doi.org/10.1002/emmm.201302505